A critical review on drying shrinkage mitigation strategies in cement-based materials. (June 2021) - Tran, Nghia P.; Gunasekara, Chamila; Law, David W.; Houshyar, Shadi; Setunge, Sujeeva; Cwirzen, Andrzej
Abstract: Drying shrinkage deformation due to moisture migration is a major concern in cementitious materials and can lead to a high probability of cracking, resulting in a deterioration in long-term performance and serviceability. In this paper, the primary mechanisms of drying shrinkage, mitigation strategies and the research gaps are elucidated to provide a comprehensive understanding of the factors influencing drying shrinkage and identify research strategies to assist in the development of novel shrinkage-resistant concrete. The use of shrinkage-reducing admixture is identified as the high-efficiency methodology. This reduces the surface tension of the liquid in the capillary pore, resulting in a 20–50% drying shrinkage reduction when applied with a dosage up to 3%. It can achieve even greater efficiency by combining the admixture with expansive agents to provide synergistic effects, giving mitigation of drying shrinkage of up to 80%. Replacing cement with supplementary cementitious materials, up to 35%, is also an effective approach to mitigate drying shrinkage, giving a reduction between 5–42%. The reinforcing effect of novel carbon-nanotubes, albeit at a small dosage (0.1% w.t), can effectively strengthen the C–S–H gel matrix, resulting in a drying shrinkage reduction of 15–21%. Introducing internal restraints using fibres or aggregate also demonstrates high effectiveness for drying shrinkage mitigation. Furthermore, coupled CO2 -water curing or coating the concrete surface to prevent moisture loss provides an innovative approach to drying shrinkage reduction at an early age (50–70%). Finally, to avert time-dependent deformation, the use of superplasticizer (less than 1%) based on the polycarboxylate polymer is suggested. Highlights: Shrinkage reducing admixture can attenuate drying shrinkage deformation by 20–50%. Surface coating or coupled CO2 -water curing mitigate drying shrinkage by 50–70%. Small amount of carbon nanomaterial help resists drying shrinkage by 7–14%. Larger the aggregate size, greater the restraining effect against drying shrinkage. Combinations of techniques could provide synergistic effects with greater efficiency.